Polyester hydrolysis is enhanced by a truncated esterase: Less is more. Issue 8 (11th October 2016) - Biundo, Antonino; Ribitsch, Doris; Steinkellner, Georg; Gruber, Karl; Guebitz, Georg M.
Abstract: An esterase from Clostridium botulinum (Cbotu_EstA) previously reported to hydrolyze the biodegradable polyester poly(butylene adipate‐ co ‐terephthalate) was redesigned to improve the hydrolysis of synthetic polyesters. Increased activity was indeed observed for del71Cbotu_EstA variant, which performed activity on the widespread polyester polyethylene terephthalate, which was not able to be attacked by the wild‐type enzyme Cbotu_EstA. Analysis of the 3D structure of the enzyme showed that removing 71 residues at the N‐terminus of the enzyme exposed a hydrophobic patch on the surface and improved sorption of hydrophobic polyesters concomitantly facilitating the access of the polymer to the active site. These results show a new route for enhancing enzyme activity for hydrolysis and modification of polyesters. Abstract : Enzymes are able to hydrolyze the surface of polymer substrates. In this study, the authors prove that the truncation of the N‐terminus of the esterase Cbotu_EstA improves its adsorption on polyethylene terephthalate (PET) surfaces and the hydrolysis of ester bonds releasing products which can be detected to analyze the enzymatic activity.